The epidermis as an adjuvant - Gutowska-Owsiak, D; Ogg, G (2012)
It is now clear that the epidermis has an active role in local immune responses in the skin. Keratinocytes are involved early in inflammation by providing first-line innate mechanisms and, in addition, can contribute to adaptive immune responses that may be associated with clinical disease. Moreover, keratinocytes are capable of enhancing and shaping the outcome of inflammation in response to stimuli and promoting particular types of immune bias. Through understanding the underlying mechanisms, the role of keratinocytes in disease pathogenesis will be further defined, which is likely to lead to the identification of potential targets for prophylactic or therapeutic intervention. © 2012 The Society for Investigative Dermatology.